2001
DOI: 10.1021/es0016699
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Evaluation on the Effectiveness of a Catalyst Retrofit Program in China

Abstract: A low-cost, rare-earth oxide (REO) catalyst has been recommended as part of China's retrofit program for Chinese carbureted vehicles. This study evaluated: (1) the emission reduction efficiency of the REO catalyst during chassis dynamometer testing on the FTP cycle; (2) the effect that fuel properties had on tailpipe emissions and catalyst efficiency; (3) the importance of vehicle premaintenance as part of a retrofit protocol; and (4) the emission reductions obtained following implementation of the program.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Emission control systems can be either integrated in the vehicle design phase (OEM) or retrofitted on in-use vehicles . Retrofit emission control efforts have shifted from light-duty petrol vehicles to heavy-duty diesel trucks and buses over time, , as diesel vehicles are the highest contributor of PM and NO x emissions in many urban environments around the world. …”
Section: Introductionmentioning
confidence: 99%
“…Emission control systems can be either integrated in the vehicle design phase (OEM) or retrofitted on in-use vehicles . Retrofit emission control efforts have shifted from light-duty petrol vehicles to heavy-duty diesel trucks and buses over time, , as diesel vehicles are the highest contributor of PM and NO x emissions in many urban environments around the world. …”
Section: Introductionmentioning
confidence: 99%
“…According with these results, the before-1990 MY fleet as well as the 1991-1992 MY should have failed the mandatory I/M test. As a comparison, Jones et al recently reported average THC and CO exhaust concentration levels of 450 ppm and 4.5 vol %, respectively, at 2500 rpm test conditions for a group of Chinese taxis without emission controls (14). In the case of the 1993-1994 MY fleet, the normal emitters should have obtained Certificate One, the high emitters should have obtained Certificate Two, and the 1995-2000 MY fleet would be allowed to circulate all days.…”
Section: Resultsmentioning
confidence: 99%